2019
DOI: 10.1186/s13037-019-0198-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anxiety among adult patients undergoing elective surgery: a prospective survey at a general hospital in Ethiopia

Abstract: Background Major life changes are among factors that cause anxiety, and one of these changes is surgery. Hospitalization, regardless of disease, is known to provoke anxiety in the patient admitted for surgery. Anxiety is an unpleasant disturbing experience that involves way of thinking of tension, apprehension, uneasiness and high autonomic activity. Patients with high levels of anxiety require higher doses of anesthetic induction agents and recover poorly. The objective of this study was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
4
19

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 10 publications
4
91
4
19
Order By: Relevance
“…Prevalence of preoperative anxiety among surgical patients in Ethiopia was very which varied from 47-70.3% (21,(34)(35)(36) and other studies in Africa; Nigeria and Tunisia showed that the prevalence of preoperative anxiety was 51 to 90% (10,37,38) and 67.5% respectively (39).…”
mentioning
confidence: 89%
“…Prevalence of preoperative anxiety among surgical patients in Ethiopia was very which varied from 47-70.3% (21,(34)(35)(36) and other studies in Africa; Nigeria and Tunisia showed that the prevalence of preoperative anxiety was 51 to 90% (10,37,38) and 67.5% respectively (39).…”
mentioning
confidence: 89%
“…Besides, the prevalence of preoperative anxiety was 53% in Brazil, 15 63% in Pakistan, 16 67% in Tunisia, 17 and 72.8% in Rwanda. 18 In Ethiopia, preoperative anxiety is a common mental health problem and its magnitude ranges from 47% 19 to 70.3%. 20 There are only a few relevant studies on preoperative anxiety among surgical patients in developing countries, particularly in Ethiopia.…”
mentioning
confidence: 99%
“…Among these, 6 69 disregarded due to qualitative study, abstracts, and titles. Finally, this meta-analysis includes a total of 6 studies with 1832 subjects [28][29][30][31][32][33] (Figure 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Three regions and Addis Ababa was the settings studies found. Two in Oromia region [30,33], two in Amhara region [31,32], one in Addis Ababa [28], and one in Southern Nation, Nationalities, and People (SNNP) [29]. All included studies done by using the cross-sectional study design (Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation